Plasma cell-free DNA measured prior to renal replacement therapy initiation is not associated with incident adverse outcomes, hospitalizations or malignancies in chronic kidney disease stage 4–5 patients - Niilo Liuhto; Jenni Tuominen; Noora Manni; Markus Hakamäki; Roosa Lankinen; Tomi Toukola; Jonna Virtanen; Kaj Metsärinne; Mikko J. Järvisalo; Tapio Hellman (PLoS ONE, 2026)
Inflammation is an inherent feature of advanced chronic kidney disease (CKD) and associated with adverse outcomes. Several inflammatory biomarkers have been shown to be associated with mortality in CKD. Cell-free DNA (cfDNA) is a novel biomarker for inflammation which has not been previously examined in patients with CKD stage 4–5 not undergoing dialysis. cfDNA was extracted from plasma and quantified with Qubit Flex Fluorometer using dsDNA High Sensitivity kit in 138 patients with CKD stage 4–5 not undergoing dialysis at baseline and at a control time point of median 2.7 years of follow-up. A ratio of control and baseline measurement adjusted for an increment of one year of follow-up was calculated. Associations between cfDNA at baseline and all-cause mortality, major adverse cardiovascular and cerebrovascular events (MACCE, defined as a composite outcome of acute myocardial infarction, coronary revascularization, ischemic or hemorrhagic stroke and cardiovascular death), emergency room (ER) visits, hospitalizations or incident malignancies were assessed. Within a median follow-up of 6.2 years, no associations were observed between cfDNA and mortality, MACCEs, ER visits, hospitalizations or incident malignancies. cfDNA control measurement and cfDNA delta ratio was available in 101 patients. Patients who had received a kidney transplant by the control cfDNA measurement had significantly higher cfDNA delta ratio compared to patients not on renal replacement therapy (RRT) and those undergoing dialysis (p < 0.001 for both comparisons). Patients undergoing dialysis at the time of the control cfDNA measurement had higher cfDNA delta ratio (p = 0.003) compared to patients not on RRT. The present study is the first to show that cfDNA is not associated with adverse outcomes in patients with advanced CKD not undergoing dialysis at baseline. Furthermore, our results provide unique data on the evolution of cfDNA levels in predialysis CKD stage 4–5 patients transitioning to different modalities of RRT.